'Others' among 'Us': Exploring Racial Misidentification of Japanese Youth. Issue 3 (2nd September 2021) - Sato, Yuna
ABSTRACT: This article examines policing of the boundary of Japaneseness in contemporary Japan by analyzing the experiences of 15 young individuals. Despite their self-recognition as not having any foreign ancestors, they are often misrecognized as half-Japanese or non-Japanese by others. This article explores the causes and consequences of this categorization and reflects on the implications of ethnic or racial misidentification for the misidentified and for the wider society. The findings confirm that others labeled the participants as hāfu (mixed) or foreign to make sense of the inconsistency between the participants' 'non-Japanese-like' personal features and a narrow notion of Japaneseness. Their lack of Japaneseness meant the participants experienced exclusion owing to the unmarked norms in Japanese society. They were also treated as though they were hāfu or foreign. However, their belief or claim of having only Japanese ancestors often confused others as well as themselves, which resulted in various attempts to make sense of their 'differences'. This article concludes that the marginalization and othering of various ethnic or racial groups in Japan helped avoid challenging the notion of Japaneseness. Therefore, to tackle exclusion, diversity among 'majority Japanese' needs to be acknowledged.